Pakistan : Reforming Punjab's Public Finances and Institutions - World Bank (Washington, DC, 2013)
Similarly to Pakistan's other provinces, and the country as a whole, Punjab Province - a macrocosm of the country, with more than half the population, and economic activity - is facing a crisis of public service delivery, government finances, public institutions, and governance. Hence, the resulting social, and infrastructure "deficits", have contributed to slower economic growth, slower poverty reduction, and poor social indicators in the province. Nevertheless, Punjab has the opportunity to turn around its public sector, for the provincial government seems determined to improve service delivery. This report is intended to provide an input for this process, and, puts forward recommendations for fiscal restructuring, institutional improvements - including civil service reform - and, sectoral reforms to improve service delivery in education, health, agriculture and irrigation, and roads. Fiscal restructuring needs to focus the public sector on essential core roles, to include improved financial management; revamping planning, and budgeting; mobilizing revenue from taxes, and user charges; and, implementing fiscal decentralization. Institutional improvements, and civil reform would include accountability, and strengthening key provincial economic management, regulatory, and sectoral institutions, while reforms in individual sectors should improve service delivery , and development outcomes. The Federal Government should play an important role in supporting, and facilitating provincial reforms, by guiding the devolution process, stabilizing federal revenues, and, working closely with the provinces in the reform process.